2015
DOI: 10.14419/ijans.v4i2.4447
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a training program on improving the hand washing among children in primary schools

Abstract: Background: Hand washing with soap has been viewed as one of the most cost-effective ways of reducing the global infectious disease burden. Proper hand washing technique is easy to learn and can significantly reduce the spread of infectious diseases among children. Aim: the study was conducted to evaluate the effectiveness of a training program on improving the hand washing among children in primary schools. Methods: quasi experimental design was used in the study. The data was collected from 450 students, age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Parents are the primary source of knowledge to their children and their level of education influenced students' ability to know germs (Appendix A, Table 1). This is congruent with many studies that found a positive relationship between students' parents' level of education and the practice of hand washing among the students (Luby, 2005;Dongre et al, 2006;Ocaktan et al, 2010;Moussa et al, 2015). However, the effect size was relatively small (Cramer's V =0.15).…”
Section: Parents Level Of Education and Influence On Hand Washingsupporting
confidence: 88%
“…Parents are the primary source of knowledge to their children and their level of education influenced students' ability to know germs (Appendix A, Table 1). This is congruent with many studies that found a positive relationship between students' parents' level of education and the practice of hand washing among the students (Luby, 2005;Dongre et al, 2006;Ocaktan et al, 2010;Moussa et al, 2015). However, the effect size was relatively small (Cramer's V =0.15).…”
Section: Parents Level Of Education and Influence On Hand Washingsupporting
confidence: 88%
“…Children are prone to zoonotic infections due to increased physical contact with their pets [12,51] and poor hygiene practices [2,7,34]. As untreated zoonotic diseases have lifethreatening implications [19], it is imperative to understand the mechanism of infection transmission from animals to humans and practice hand hygiene as a preventive measure against these diseases [33,9].…”
Section: Introductionmentioning
confidence: 99%